2014
DOI: 10.4269/ajtmh.13-0317
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of the Effect of Mass Drug Administration on Acute Inflammatory Episodes and Disease Progression in Lymphedema Patients in Léogane, Haiti

Abstract: Abstract. We conducted a longitudinal analysis of 117 lymphedema patients in a filariasis-endemic area of Haiti during [1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008]. No difference in lymphedema progression between those who received or did not receive mass drug administration (MDA) was found on measures of foot (P = 0.24), ankle (P = 0.87), or leg (P = 0.46) circumference; leg volume displacement (P = 0.09), lymphedema stage (P = 0.93), or frequency of adenolymphangitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…FR-LE studies which provided frequent monitoring and support were associated with greater improvements than studies which offered minimal or no support services. The study by Suma, Shenoy [ 55 ] which retrospectively reviewed participants in a previous drug based RCT indicated that without monitoring, program effectiveness is lost over time, an effect also found in a later follow up of the study by Addiss, Louis-Charles [ 36 ] which could not be included in this review [ 61 ]. Ultimately, the long term success of any self-care intervention will depend on individual ownership of and adherence to the daily self-care practices and the level of family or local support available.…”
Section: Discussionmentioning
confidence: 99%
“…FR-LE studies which provided frequent monitoring and support were associated with greater improvements than studies which offered minimal or no support services. The study by Suma, Shenoy [ 55 ] which retrospectively reviewed participants in a previous drug based RCT indicated that without monitoring, program effectiveness is lost over time, an effect also found in a later follow up of the study by Addiss, Louis-Charles [ 36 ] which could not be included in this review [ 61 ]. Ultimately, the long term success of any self-care intervention will depend on individual ownership of and adherence to the daily self-care practices and the level of family or local support available.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a number of incidents during field work suggested that some individuals with chronic morbidity in the later part of the study hid themselves to avoid examination, as previous examinations had not provided alleviation of their disease symptoms. Several cross-sectional follow-up studies in the past have suggested that DEC might have a positive effect on lymphedema and hydrocele, but cohort studies following individual patients over a period of time have not been able to confirm this [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute adenolymphangitis, or acute dermatolymphangioadenitis (ADLA), known commonly as ‘acute attacks’, is the term used to describe recurrent inflammatory episodes in lymphoedema [17]. ADLA is most likely triggered by skin lesions acting as entry points for bacteria, fungi or viruses, although often no clear cause is identified [18,19]. Episodes are typically characterized by hot, painful and reddened swelling of the leg, chills, malaise, anorexia and sometimes lower leg skin peeling, and are one of the most serious complications of podoconiosis; resulting in worsening disability [8, 20].…”
Section: Introductionmentioning
confidence: 99%